2016
DOI: 10.2147/prbm.s112421
|View full text |Cite
|
Sign up to set email alerts
|

Grappling with the issue of homosexuality: perceptions, attitudes, and beliefs among high school students in Kenya

Abstract: While the past decade has seen an improvement in attitudes toward homosexuality, negative attitudes are still prevalent in many parts of the world. In general, increased levels of education tend to be predictive of relatively positive attitudes toward homosexuality. However, in most sub-Saharan countries, it is still believed that people are born heterosexual and that nonheterosexuals are social deviants who should be prosecuted. One such country is Kenya, where homosexuality is illegal and attracts a fine or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Even though negative attitudes towards homosexuals decrease with higher education levels, in sub-Saharan countries, homosexuals are still regarded as perverts who should be put on trial. Homosexuality is punishable by fines and imprisonment in Kenya (Mucherah, Owino, & McCoy, 2016).…”
mentioning
confidence: 99%
“…Even though negative attitudes towards homosexuals decrease with higher education levels, in sub-Saharan countries, homosexuals are still regarded as perverts who should be put on trial. Homosexuality is punishable by fines and imprisonment in Kenya (Mucherah, Owino, & McCoy, 2016).…”
mentioning
confidence: 99%
“…This study agreed with the previous study that showed having a good level of knowledge about homosexuals in new students is expected to reduce discrimination in health services and to increase awareness in the society about causes and concequences of homosexuals. 4,14 .…”
Section: Discussionmentioning
confidence: 99%
“…Findings by Mucherah, Owino, and McCoy (2016) in a study conducted in Kenyan high schools indicated that while the students were ill-informed, they did perceive that homosexuality exists in their schools. The students also believed that homosexuality is mostly practiced in single-sex boarding schools, especially boys' boarding schools, and were of the opinion that homosexuality in schools is influenced by "sexual starvation."…”
Section: Perception Of Sexual Minoritiesmentioning
confidence: 99%
“…The students recommended that peers found culpable should be expelled. Mucherah et al (2016) found that more females than males affirmed that homosexuality exists in their schools. This is contrary to the boys' opinion that homosexuality is more prevalent in the all-boys' boarding schools.…”
Section: Perception Of Sexual Minoritiesmentioning
confidence: 99%